Siri Marriage In The Review of Islamic Law, Positive Law, Human Rights And Maqashid Al-Syari'ah - Ishaq Ishaq; Badarussyamsi Badarussyamsi; Suhar AM; Muannif Ridwan (Studi Multidisipliner: Jurnal Kajian Keislaman, 2023)
The issue of siri marriage is a conflict of norms, namely the norms of Islamic law, marriage law, human rights, and Maqashid al-Syariah. So that its existence that develops in society there are pros and cons. This research is a literature research using the Maqasid al-Syari'ah approach as an analytical tool. The findings of this study state that siri marriage according to the provisions of Islamic Law is valid, while positive law states that it is invalid (void) or can be canceled. As for human rights, siri marriage is not against the law, because the issue of marriage is a basic right for humans which is a gift from God and it has been regulated in the constitution (1945 Constitution) as well as in Law Number 39 of 1999 concerning human rights. While Maqashid al-Syari'ah views siri marriage as an act that can cause harm, then to prevent it from being registered with the authorities, it is based on the method of al-maslahah al-mursalah and sadd al-zari'ah considering that marriage has a fixed law as a means of realizing benefit